Pengaruh Kondisi Keuangan dan Politik Terhadap Perubahan Anggaran pada Pemerintah Daerah di Indonesia - Agus Purwanto (Jurnal Akuntansi dan Bisnis, 2016)
The purpose of this study is to obtain empirical evidence of the influence of financial autonomy, the accumulated surplus, revised surplus, political fragmentation and the years since the election of the budget changes districts/cities in Indonesia. The sample using the 59 districts/cities in Indonesia in 2012-2014. Sampling was done by using purposive sampling method. The analytical method used is multiple linear regression analysis models were performed with SPSS version 22.00. Results of regression testing showed that the accumulated surplus and financial autonomy have positive influence on changes to the budget, while the revised surplus have negative influence on budget changes. Political fragmentation and a year since the election have no effect on the budget changes.